I am going! The Facebook’s users’ attendance to events as a performative political act in Occupy Estelita Movement - SANTOS, Caio de Castro Mello (2018)
SANTOS, Caio de Castro Mello, também é conhecido(a) em citações bibliográficas por: MELLO, C. C.